Dose Effect and Mode of Inheritance of Diabetogenic Gene on Mouse Chromosome 11 - Naru Babaya; Hironori Ueda; Shinsuke Noso; Yoshihisa Hiromine; Koji Nojima; Michiko Itoi-Babaya; Misato Kobayashi; Tomomi Fujisawa; Hiroshi Ikegami (Journal of Diabetes Research)
The quantitative trait locus (QTL) mapping in segregating crosses of NSY (Nagoya-Shibata-Yasuda) mice, an animal model of type 2 diabetes, with nondiabetic strain C3H/He mice has identified diabetogenic QTLs on multiple chromosomes. The QTL on chromosome 11 (Chr11) (Nidd1n) showing the largest effect on hyperglycemia was confirmed by our previous studies with homozygous consomic mice, C3H-11NSY, in which the NSY-derived whole Chr11 was introgressed onto control C3H background genes. C3H-11NSY mice also showed a streptozotocin (STZ) sensitivity. In the present study, we constructed heterozygous C3H-11NSY mice and the phenotypes were analyzed in detail in comparison with those of homozygous C3H-11NSY and C3H mice. Heterozygous C3H-11NSY mice had significantly higher blood glucose levels and STZ sensitivity than those in C3H mice. Hyperglycemia and STZ sensitivity in heterozygous C3H-11NSY mice, however, were not as severe as in homozygous C3H-11NSY mice. The body weight and fat pad weight in heterozygous C3H-11NSY mice were similar to those in C3H and homozygous C3H-11NSY mice. These data indicated that the introgression of Chr11 of the diabetes-susceptible NSY strain onto diabetes-resistant C3H caused marked changes in the glucose tolerance and STZ susceptibility even in a heterozygous state, and suggested that the mode of inheritance of a gene or genes on Chr11 for hyperglycemia and STZ sensitivity is additive.